Electronic structure of bispentalene complexes of titanium, zirconium, and hafnium: a photoelectron spectroscopic study - Gleiter, Rolf; Bethke, Sabine; Okubo, Jun; Jonas, Klaus (Organometallics, 2001)
The geometrical parameters of the bis(pentalene) complexes of titanium, zirconium, and hafnium (3a−c) have been calculated by applying the RHF method. For 3a a structure with C1 symmetry results, whereas for 3b,c D2 symmetry is predicted. The torsional angles between the two pentalene ligands are calculated to be 56° (3a), 51° (3b), and 50° (3c). The orbital sequence of the six highest occupied molecular orbitals agrees very well with the ionization energies measured by PE spectroscopy of 3a−c. These measurements support a structure with D2 or closely related symmetry.